Heme Oxygenase Dependent Bilirubin Generation in Vascular Cells: A Role in Preventing Endothelial Dysfunction in Local Tissue Microenvironment? - Nitti, Mariapaola; Furfaro, Anna Lisa; Mann, Giovanni E. (Frontiers in Physiology, 2020)
Among antioxidants in the human body, bilirubin has been recognized over the past 20 years to afford protection against different chronic conditions, including inflammation and cardiovascular disease. Moderate increases in plasma concentration and cellular bilirubin generation from metabolism of heme via heme oxygenase (HMOX) in virtually all tissues can modulate endothelial and vascular function and exert antioxidant and anti-inflammatory roles. This review aims to provide an up-to-date and critical overview of the molecular mechanisms by which bilirubin derived from plasma or from HMOX1 activation in vascular cells affects endothelial function. Understanding the molecular actions of bilirubin may critically improve the management not only of key cardiovascular diseases, but also provide insights into a broad spectrum of pathologies driven by endothelial dysfunction. In this context, therapeutic interventions aimed at mildly increasing serum bilirubin as well as bilirubin generated endogenously by endothelial HMOX1 should be considered.